Exploring Educational Dynamics in Conflict-Affected Areas of Southern Thailand: A Qualitative Case Study with an Islamic Education Approach: - - Adri Efferi; Kuntarno Noor Aflah; Oki Dermawan; Islahuddin Islahuddin; Mahamadaree Waeno (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
The ongoing conflict between the central Thai government and the predominantly Muslim provinces of Southern Thailand, particularly Yala, Pattani, and Narathiwat, has significantly impacted various sectors, including education. The ethnic and religious divisions inherent in this conflict have posed challenges to implementing educational policies. This study explores how local elite politics influence the integration of Islamic education and the national curriculum in these conflict-prone areas. A qualitative case study approach was employed, utilizing semi-structured interviews, observations, and document analysis to gather data from key stakeholders, including school leaders, policymakers, and educators. The findings reveal that despite efforts to incorporate religious and secular curricula, local educational systems face persistent challenges in maintaining balance amidst the broader socio-political tensions. This study also highlights the role of local elite politics in shaping educational policies, particularly in the context of religious and cultural identity. It underscores the need for more flexible and culturally inclusive educational policies that not only meet national standards but also respect the unique cultural and religious needs of the Muslim community in Southern Thailand. The novelty of this research lies in its focus on the intersection of local politics, education, and conflict in a qualitative context, offering new insights into how education can be leveraged as a tool for peacebuilding and social cohesion in conflict-affected regions.